Comparison of structural, textural and thermal characteristics of pure and acid treated bentonites from Aleksinac and Petrovac (Serbia) - Tomić, Zorica P; Logar, Vesna P; Babic, Biljana M; Rogan, Jelena R; Makreski, Petre (Elsevier BV, 2011)
Bentonite samples collected from vicinity of Petrovac and Aleksinac were treated with different sulfuric acid molarities. Acid attack dissolved the octahedral sheets by interlayer and edge attack. The effects of the H(2)SO(4) acid caused an exchange of Al(3+), Fe(3+) and Mg(2+) with H(+) ions leading to a modification of the smectite crystalline structure. The Mg and Fe substitution in the octahedral sheets promoted the dispersion of corresponding layers and formation of amorphous silicon. The activated bentonites, after the treatment of sulfuric acid, exhibited a lower cation-exchange capacity (CEC) and significant increase of specific surface area from 6 to 387 m(2) g(-1) (bentonite from Petrovac) and from 11 to 306 m(2) g(-1) (bentonite from Aleksinac). The acid reaction caused a splitting of particles within the octahedral sheet which led to an increase in specific surface area and decrease in CEC in both bentonites.